2024
DOI: 10.3390/buildings14020321
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Neutrality in the Building Sector of the Global South—A Review of Barriers and Transformations

Elnaz Ghasemi,
Rahman Azari,
Mehdi Zahed

Abstract: This work provides a review of economic, technical, sociocultural, political, and technological barriers that impede carbon neutrality in the building sector of countries in the Global South. These barriers include limitations in public and professional awareness, knowledge, and skills in the construction industry, the lack of ambitious energy codes and green building rating systems, the lack of green financing schemes and investment, costs of materials and technology, and limitations in regulations. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…While the building and construction industry continues to struggle to achieve the net zero emissions targets, our review of the literature found a very limited number of review articles on the challenges related to the carbon neutrality transition in the building and construction industry. Some review papers limited their scope to a particular geographical region, such as developing countries, the global south [16], and China [17]. Some others discussed only one aspect of net zero emissions building, such as energy efficiency [18], renewable energy generation [19], etc., or had a holistic view of the barriers without concentrating on any specific stage of the building lifecycle or stakeholder groups that experience them [16,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the building and construction industry continues to struggle to achieve the net zero emissions targets, our review of the literature found a very limited number of review articles on the challenges related to the carbon neutrality transition in the building and construction industry. Some review papers limited their scope to a particular geographical region, such as developing countries, the global south [16], and China [17]. Some others discussed only one aspect of net zero emissions building, such as energy efficiency [18], renewable energy generation [19], etc., or had a holistic view of the barriers without concentrating on any specific stage of the building lifecycle or stakeholder groups that experience them [16,20].…”
Section: Introductionmentioning
confidence: 99%
“…Some review papers limited their scope to a particular geographical region, such as developing countries, the global south [16], and China [17]. Some others discussed only one aspect of net zero emissions building, such as energy efficiency [18], renewable energy generation [19], etc., or had a holistic view of the barriers without concentrating on any specific stage of the building lifecycle or stakeholder groups that experience them [16,20]. No recent review article was found to focus on the barriers and challenges that organisations face in the delivery of new net zero emissions buildings from initiation till the end of the construction stage.…”
Section: Introductionmentioning
confidence: 99%